1980
DOI: 10.1115/1.3230225
|View full text |Cite
|
Sign up to set email alerts
|

On Flame Stabilization by Bluff-Bodies

Abstract: Flame stabilization by bluff-bodies has been investigated to highlight the role of recirculation zone on the phenomenon. It has been observed that close correlations exist between heat exchange from recirculation zone and flame stability as controlled by recirculation strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In addition, Kundu et al's. [100,101] measurements show a monotonic reduction of temperature in the recirculation zone as the flow velocity increases toward its blowoff value. They found that the ratio of wake to adiabatic flame temperature decreased from 0.94 to 0.88 as U/U LBO increased from 0.3 to 0.9.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, Kundu et al's. [100,101] measurements show a monotonic reduction of temperature in the recirculation zone as the flow velocity increases toward its blowoff value. They found that the ratio of wake to adiabatic flame temperature decreased from 0.94 to 0.88 as U/U LBO increased from 0.3 to 0.9.…”
Section: Discussionmentioning
confidence: 94%
“…Since entrainment rates scale as D/U (see Section 2.2.2) then it follows that this criterion reduces to a Damkö hler number blowoff criterion, using a chemical time that is derived from the well stirred reactor, s PSR . A similar idea relates to an energy balance between heat supplied by the hot recirculating flow to the fresh gases and that released by reaction [98,[100][101][102]. In this view, blowoff occurs when the heat required by the combustible stream exceeds that received from the recirculation zone.…”
Section: Discussionmentioning
confidence: 98%
“…LBO scaling as a function of combustion parameters (incoming flow velocity, equivalence ratio, pressure, temperature, and fuel type) have been reported for specific combustor configurations [9][10][11][12][13][14], and active or passive control strategies to extend LBO have been explored [8,[15][16][17][18]. Several LBO mechanisms have been proposed and include balance between the rate of entrainment of reactants into the recirculation zone and the rate of buming [19], energy balance between heat supplied by the hot recirculating flow to the fresh gases and that released by reaction [20][21][22][23], balance between contact time between the combustible mixture and hot gases in the shear layer and chemical ignition time [20,[24][25][26], and mecha-nisms related to local extinction by excessive flame stretch with a flamelet based description [27][28][29]. In addition, it is believed that flame front instabilities play important roles in the blowout process in view of the reported observations of flame pulsations and flicker before the flame actually blows out [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of the mass-weighted velocities is explained in the description of Eqns. (1) and (2). The mass-weighted velocity does not coincide with the flow velocity itself.…”
Section: Stability Curve Of Bluff-body Stabilized Flamesmentioning
confidence: 99%
“…The relation between flame structure and flame stability was identified. Kundu et al [2] investigated flame stabilization by bluff-bodies to highlight the role of the recirculation zone. They observed that close correlations exist between heat exchange from the recirculation zone and flame stability, which were controlled by the strength of recirculation.…”
Section: Introductionmentioning
confidence: 99%